Practical Training of Students-Ecologists toEnvironmental Education and Upbringing of School Children - Nataliya Kazanishena (Pedagogical Discourse, 2013)
The article emphasizes on the problem of organizing and optimizing of pedagogical practice  of students- environmentalists. The importance of pedagogical practice in the process of becoming a specialist is cleared. The functions, objectives and principles of its organization are rflected. The stages of practice are offered and charactrized. Complex tasks that students perform during practice is worked out. Educational and skill requirements for training students- environmentalists are taken into account. The list of statements, the requirements for their execution are given. The conclusion about the role of systematic teaching practice of students environmentalists and effectiveness of the proposed methods is made.